Identification of aroma, earthy flavour and aftertaste in tilapia using sensory evaluation technique - Bakar, Jamilah; Ahmad, Nurul Izzah; Yusoff, Salmah; Ahmad, Faujan (Universiti Putra Malaysia Press, 2001)
Trained panelists were used to identify the flavour profile which consists of aroma, flavour and aftertaste of wild black tilapia (Oreochromis mossambica). For the purpose of comparison, 2 marine fish namely Indian mackerel(Rastrelinger kanagurta) and bonito (Euthynnus affins) and catfish (Clarias batrachus), a freshwater fish, were also evaluated. Ten and eight aroma, flavour and aftertaste attributes respectively were recognized in tilapia. However, the presence of kerosine-like attribute could be due to petrochemical contaminants. The presence of strong to moderate earthy attribute is dominantly recognized in its aroma and flavour which are consistently scored higher than that in catfish except for the aftertaste. The presence of geosmin in the tilapia muscle could most probably be in the range of 1. 0 to 10.0 mg-1. The earthy aroma may be reduced upon cooking.